Pengelolaan ICT Sebagai Media Pembelajaran IPA di SD Negeri 1 Tunggak Kecamatan Toroh Kabupaten Grobogan - Mustofa, Moch Ali; , Prof. Dr. Bambang Sumardjoko; , Dr. Sumardi, M.Si (2016)
ABSTRACT Moch Ali Mustafa. Q.100.140.079. Management of ICT as a medium of learning science in SD Negeri 1 Tunggak Toroh Subdistrict Grobogan. Thesis. Graduate Muhammadiyah University of Surakarta. 2015. The purpose of this research was to determine (1) to describe the characteristics of ICT Planning as a medium of learning science at SD Negeri 1 Tunggak. (2) to describe the characteristics of ICT Application as a medium of learning science at SD Negeri 1 Tunggak. (3) to describe the characteristics of ICT Assessment as a medium of learning science at SD Negeri 1 Tunggak. This research is a qualitative research conducted at SD Negeri 1 Tunggak Toroh Subdistrict Grobogan Regency. Data collection techniques used observation, interview and documentation. Data analysis technique performed with data collection, data reduction, data presentation, and conclusion. The validity test of the data in this study used sources triangulation. The results of this study were (1) Teacher of SD Negeri 1 Tunggak planned ICT as a learning medium of Science to prepare the material and then make a material presentation of ICT, they are images, videos and real animations. Availability of facilities supporting ICT infrastructures is enough, with the availability of electricity resources, Laptop, LCD, internet modem, projection screens and enough classrooms. (2) The implementation of ICT as a learning medium started from the preparation of the material as outline in the lesson plan. The material shown in the form of pictures, video or animation, taken from google animation, video get by downloading from YouTube. Implementation of learning using ICT as a medium of learning science makes students enthusiastic in participating and giving response in learning. (3) ICT assessment as a medium of science subjec at SD Negeri 1 Tunggak considers the following matters: a) effective and efficient, b) Optimal, c) attractive, d) stimulate creativity of students think. Use of ICT as medium in learning science at SD Negeri 1 Tunggak also considers the principles of selection of learning medium. Keywords: ICT, media, science